2018
DOI: 10.1111/acer.13603
|View full text |Cite
|
Sign up to set email alerts
|

Text Messaging to Reduce Alcohol Relapse in Prelisting Liver Transplant Candidates: A Pilot Feasibility Study

Abstract: Participants reported high satisfaction with the intervention, looked forward to the messages, and found it easy to complete. Participants who received the intervention had better treatment outcomes than those who received standard care. They maintained higher levels of self-efficacy and lower stress. Mobile alcohol interventions may hold significant promise to help ALD liver transplant patients maintain sobriety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 45 publications
0
47
0
3
Order By: Relevance
“…Search procedures (Figure ) yielded 471 unique abstracts (1986‐2018), 75 full‐text articles screened, and 11 eligible reports from 10 unique research teams. Reports included 2 completed and 1 failed randomized trial, and 8 observational studies (3 prospective and 5 retrospective) . Refer to Table for study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Search procedures (Figure ) yielded 471 unique abstracts (1986‐2018), 75 full‐text articles screened, and 11 eligible reports from 10 unique research teams. Reports included 2 completed and 1 failed randomized trial, and 8 observational studies (3 prospective and 5 retrospective) . Refer to Table for study characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…DeMartini et al reported the first test of a technology‐based relapse prevention intervention. Researchers randomly assigned 15 transplant candidates to receive an 8‐week text messaging intervention in addition to psychological addiction counseling, or psychological addiction counseling alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There has only been 1 peer‐reviewed study to date exploring the use of a digital intervention for individuals with ALD and AUD. DeMartini and colleagues () randomly assigned pre liver transplant candidates with alcoholic liver disease who reported at least 1 drinking episode in the past year to either receive 3 messages per day for 4 weeks and 3 messages per week for 4 weeks including feedback on cravings, mood, identification of high‐risk situations and coping ( n = 8), or no intervention ( n = 7). Main findings were that the SMS intervention was well received by participants and resulted in 0 of 8 participants with positive urine alcohol at 8 weeks versus 2 control participants.…”
Section: Sms‐based Intervention Studies For Audmentioning
confidence: 99%